Urban Rehabilitation as an Integration in the City: Analysis from the Spanish Experience - Matesanz Parellada, Ángela (2016)
In the European context of economic, social and environmental crisis, we find the Spanish case where its context is hardly worse, as consequences of an economic model based on real estate market. From this point the European Union’s commitment advocates the Integrated Urban Regeneration framed in the overall context of the strategy for Integrated Sustainable Urban Development (MHAP, 2015). Moreover, both strategies establish some continuity with the line of area-based urban interventions with integrated approach promoted by European programs and targeted on disadvantaged neighbourhoods. Equally the vision of the city as a whole and the necessary balance between its parts has been incorporated to them. This last issue, treated so far in a context with falling interest in planning, requires a new analysis framework to assess the actions taken and also to date and serve as a basis for developing new proposals.Therefore, it is considered the urgency in defining a new model of urban rehabilitation in Spain, which integrates sectoral policies and the (real) participation of all actors, so that, the paper will be based on the need of the neighbourhood’s integration into the city. It is also purposed a possible base of analysis for such integration, which might improve or get over the current urban policy interventions in neighbourhoods.